O CURSO DE PEDAGOGIA DA UNIVERSIDADE ESTADUAL DO MARANHÃO: um olhar inclusivo na formação dos alunos - Sousa, Dolores Cristina (2012)
Teacher training is indicated as one of the essential elements in building an inclusive education system. From this finding of this study was to investigate the formation process of teaching students of Pedagogy Maranhão-UEMA/campus State University of São Luís, developed in the context of the effectiveness of inclusive education policies and legislation arising therefrom adopted by the Brazilian state. Elencaram specific objectives are: to reflect on some peculiarities that underpin the process of inclusion in UEMA; identify disciplines of pedagogy that allow visualization of the deal with diversity; see what knowledge and skills are used in the training course for their students an inclusive perspective, analyze the arguments used by teachers to justify the inclusion or not of content on the education of people with special educational needs. Sought, in the official documents - concatenating them to theoretical about inclusion and teacher training - indicators that contribute in this proposed research training and realize if this course meets the requirements and official guidance when it comes to dealing with diversity, considering the National Curriculum Guidelines for the Faculty of Education and Basic Education. As a theoretical perspective was used contributions from: Sassaki (1999), Mantoan, (1998, 2002, 2006), Mittler (2003), Mendes (2002) Freitas (2006), Garcia (1999), Libâneo (1996, 1999; 2002), Pepper (2007), Carvalho (2008), among others. To carry out the investigation was chosen descriptive qualitative research, using as instruments to collect data to document analysis, semi-structured interview and questionnaire. The subjects involved consisted of nine teachers, course director and sixty-four students of Pedagogy. In the treatment and analysis of the data was made using the method of content analysis. The results showed that the work done by teachers to school inclusion is still not a principle that guides the process of restructuring the curriculum and that despite this content or discipline while most teaching plans, has guided the process of student education the inclusive perspective, demonstrating that this appears in his Political Pedagogical Project only as compliance with official regulations. The study also showed that the interviewed teachers recognize the importance of an education based on theoretical grounds that offer future teachers a framework for more focused analysis and reconstruction of practices aimed at students with Special Educational Needs. In this sense, was contacted to talk about school inclusion is to rethink the meaning that is attributed to education and the challenge posed to the Faculty of Education of UEMA, then, is to train educators who are not only instruments of knowledge transfer, but especially for new attitudes to human diversity.